CuPcs / MOR composite photocatalytic material as well as preparation method and application thereof

Through the synergistic action of CuPcs/MOR composite photocatalytic materials, the problems of narrow response range and low specific surface area of ​​existing metal oxide photocatalysts are solved, efficient NOx degradation is achieved, and the application performance of photocatalysts is improved.

CN119281396APending Publication Date: 2025-01-10XIJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411312253.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing metal oxide photocatalysts have narrow response ranges and low specific surface area in the visible light region, resulting in low NOx elimination efficiency, limiting their application in the field of photocatalytics.

Method used

CuPcs/MOR composite photocatalytic material is used to promote charge separation and transfer and improve the degradation efficiency of NOx through the synergistic effect of photocatalytic oxidation and adsorption during the reaction.

Benefits of technology

High degradation efficiency of NOx is achieved, and CuPcs reacts with oxygen molecules under light irradiation to generate active substances, increase the ·OH content in the catalytic system, effectively oxidize and degrade nitrogen oxides, and improve catalytic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281396A_ABST
    Figure CN119281396A_ABST
Patent Text Reader

Abstract

The invention discloses a CuPcs / MOR composite photocatalytic material and a preparation method and application thereof.The preparation method includes the steps that MOR powder is prepared, and then the CuPcs / MOR composite photocatalytic material is prepared from phthalic anhydride, urea, ammonium molybdate, anhydrous cuprous chloride and the MOR powder through condensation reflux with kerosene as a solvent through a one-pot method; through the synergistic effect of photocatalytic oxidation and adsorption in the reaction process of CuPcs and MOR, efficient photocatalytic degradation efficiency is achieved on NOx, and enrichment of nitric oxide is facilitated through MOR in the composite material; mOR can be used as an electron acceptor to accept electrons generated by CuPcs and induce generation of active oxygen, and charge separation can be effectively promoted; meanwhile, CuPcs serves as a photosensitizer, charge transfer can be formed between CuPcs and a small amount of CuO generated in the preparation process, and the photogenerated charge separation and transfer efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials and relates to photocatalytic materials, and in particular to a CuPcs / MOR composite photocatalytic material and a preparation method and application thereof. Background Art

[0002] With the rapid development of economy and industrialization, environmental problems are becoming more and more serious, and severe smog weather has aroused widespread public concern. Nitrogen oxides (NOx), as one of the precursors of smog, may cause acid rain and threaten human health, so effective methods are needed to reduce NOx. Liquid absorption, solid absorption, catalytic reduction and biological methods have been widely studied in post-treatment NOx technology. However, these technologies still have problems. For example, the addition of reducing agents in high-temperature reactions can cause instrument corrosion, easily cause secondary pollution, and have relatively low catalytic efficiency. Therefore, researchers use electrical energy, thermal energy, solar energy and other driving methods to make the prepared catalysts eliminate gaseous pollutants more gently. Among them, photocatalytic technology is an effective and environmentally friendly method that uses solar energy to convert and remove NOx from the air at ambient temperature and pressure.

[0003] At present, photocatalysts used to eliminate NOx are mainly photocatalytic materials based on metal oxides, such as titanium dioxide, bismuth oxide and tungsten oxide. However, most metal oxides have a narrow response range in the visible light region and a low specific surface area, which not only leads to a decrease in the elimination efficiency of NOx, but also limits the application of metal oxides in the field of photocatalysis. Summary of the invention

[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a CuPcs / MOR composite photocatalytic material with high NOx photocatalytic degradation efficiency and a preparation method and application thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a CuPcs / MOR composite photocatalytic material comprises the following steps:

[0007] Step 1: Sodium hydroxide, deionized water, seed directing agent, sodium aluminate and silica sol are mixed in a weight ratio of (0.36-0.4): (4.34-4.4): (15.6-16): (0.74-0.75): 6.5, and stirred at 20-35° C. for 20-30 hours to form a MOR synthesis system;

[0008] The MOR synthesis system was transferred to a high-pressure reactor, crystallized at 170°C for 10 h, and then filtered. The obtained solid was calcined at 550°C for 8 h to obtain MOR powder.

[0009] The components in the seed directing agent and their corresponding molar ratios are 2.8Na2O:Al2O3:17SiO2:400H2O:2TEABr;

[0010] Step 2, phthalic anhydride, urea, and ammonium molybdate are taken as precursors in a molar ratio of (20-25):10:1, the precursors are ground, and then anhydrous cuprous chloride is added according to a molar ratio of anhydrous cuprous chloride to ammonium molybdate of (8-9):1, and MOR is added according to a weight ratio of anhydrous cuprous chloride to MOR prepared in step 1 of 0.85:(1-3), stirred until mixed evenly, and then transferred to a three-necked flask, and kerosene is added according to a weight volume ratio of the precursor to kerosene of 10g:(60-70)mL, and stirred and condensed and refluxed at 185°C under nitrogen atmosphere protection for 4.5h. When the color of the product in the bottle changes from malachite green to blue-green, cool, filter, and wash to obtain a solid collection, and then boil the solid collection in 2w% hydrochloric acid solution and 2wt% sodium hydroxide solution in turn, and finally wash and dry to obtain a CuPcs / MOR composite photocatalytic material.

[0011] The present invention also has the following technical features:

[0012] Preferably, the preparation step of the seed directing agent in step 1 comprises:

[0013] Tetraethylammonium bromide, deionized water, sodium hydroxide, sodium aluminate and silica sol are taken in a weight ratio of 1.02:17.36:0.32:0.57:8.5, tetraethylammonium bromide, deionized water, sodium hydroxide and sodium aluminate are mixed, and silica sol is added after stirring evenly. After continuing to stir at 20-30°C for 5-6 hours, a reaction solution is obtained, and the reaction solution is transferred to a high-pressure reactor, aged at 100°C for 15-16 hours to obtain an aged solution, and after cooling to room temperature, the aged solution is mixed with diatomaceous earth in a weight ratio of 2:1, and dried to obtain a seed directing agent.

[0014] Furthermore, the drying condition is drying at 50-70° C. for 5-10 hours.

[0015] Preferably, the molar ratio of the components and their corresponding systems in the MOR synthesis system described in step 1 is 6Na2O:Al2O3:30SiO2:500H2O.

[0016] Preferably, the particle size of the MOR powder in step 1 is 8 to 10 μm.

[0017] Preferably, the precursor in step 2 is ground to a particle size of 200-100 μm.

[0018] Preferably, the cleaning in step 2 is performed by washing with ethanol and acetone for 3 to 5 times respectively.

[0019] Preferably, the washing in step 2 is washing with deionized water for 3 to 5 times.

[0020] The present invention also protects a CuPcs / MOR composite photocatalytic material prepared by the method as described above and its application in photocatalytic elimination of NOx.

[0021] Compared with the prior art, the present invention has the following technical effects:

[0022] The present invention successfully synthesized the CuPcs / MOR composite photocatalytic material through a one-pot method, and the high degradation efficiency of the material for NOx is attributed to the synergistic effect of photocatalytic oxidation and adsorption during the reaction process: when NO2 gas molecules pass through the adsorption layer of MOR, they are adsorbed on the surface of MOR and interact with water molecules in MOR to form NO and HNO3; under light irradiation, NO2 is photodecomposed into NO and O, and MOR zeolite can inhibit the recombination of carriers as an electron acceptor. CuPcs as a photooxidant is converted into a singlet state 1CuPcs* under irradiation and reacts with ground-state oxygen molecules to generate free radicals, some of which are converted into triplet metal phthalocyanine (3CuPcs*); the reaction between 3CuPcs* and the substrate produces active substances, and then 3CuPc* reacts with ground-state oxygen molecules to generate superoxide radicals (·O2 - ), and further converted into hydroxyl radicals (·OH), thereby acting on pollutants; at the same time, CuPcs, as a sensitizer, can transfer electrons to CuO, and the holes generated in the valence band of CuO participate in the reaction to form hydroxyl radicals (·OH), increasing the content of ·OH in the catalytic system; ultimately, both superoxide radicals and hydroxyl radicals contribute to the oxidation and degradation of nitrogen oxides to achieve the purpose of eliminating pollutants; MOR in the composite material is beneficial to the enrichment of nitrogen oxides; MOR can act as an electron acceptor to accept the electrons generated by CuPcs and induce the generation of reactive oxygen species, which can effectively promote charge separation; at the same time, CuPcs, as a photosensitizer, forms charge transfer between it and the small amount of CuO generated during the preparation process, which is beneficial to improving the efficiency of photogenerated charge separation and transfer. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the synthesis of CuPcs / MOR composite photocatalytic materials in Examples 1 to 5;

[0024] Figure 2 The CuPcs prepared in Example 3 0.85 X-ray diffraction patterns of / MOR2 composite photocatalytic materials, CuPcs and MOR;

[0025] Figure 3 The CuPcs prepared in Example 3 0.85 Fourier transform infrared spectra of / MOR2 composite photocatalytic material, CuPcs and MOR.

[0026] Figure 4 (a) CuPcs, (b) MOR and (c) CuPcs prepared in Example 3 0.85 / MOR2 composite photocatalytic material XPS full spectrum;

[0027] Figure 5 (a) CuPcs and (b) CuPcs prepared in Example 3 0.85 High-resolution Cu2p spectrum of / MOR2 composite photocatalytic material;

[0028] Figure 6 (a, b) MOR, (c) CuPcs, (d) CuPcs prepared in Example 3 0.85 / MOR2 SEM (scanning electron microscope); (e) CuPcs 0.85 TEM image (transmission electron microscope image) of / MOR2; (f)CuPcs 0.85 / HRTEM image (high magnification transmission electron microscope image) of MOR2;

[0029] Figure 7 (a) CuPcs, (b) MOR and (c) CuPcs prepared in Example 3 0.85 / N2 adsorption-desorption isotherm curve of MOR2;

[0030] Figure 8 (a) is the degradation rate of NO2 by different CuPcs / MOR composite photocatalysts at 120 min, (b) is the degradation rate of CuPcs and CuPcs 0.85 / The NO2 degradation rate of MOR2 changes with time;

[0031] Fig. 9 The CuPcs prepared in Example 3 0.85 / MOR2 recycling results diagram;

[0032] Fig.10 The CuPcs prepared in Example 3 0.85 Scanning electron micrographs of / MOR2 before and after the photocatalytic reaction. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] This embodiment provides a method for preparing a CuPcs / MOR composite photocatalytic material, comprising the following steps:

[0036] Step 1: Take tetraethylammonium bromide, deionized water, sodium hydroxide, sodium aluminate and silica sol in a weight ratio of 1.02:17.36:0.32:0.57:8.5, mix tetraethylammonium bromide, deionized water, sodium hydroxide and sodium aluminate, add silica sol after stirring evenly, continue stirring at 20°C for 5 hours to obtain a reaction solution, transfer the reaction solution to a high-pressure reactor, age at 100°C for 15 hours to obtain an aged solution, cool to room temperature, mix the aged solution with diatomaceous earth in a weight ratio of 2:1, and dry at 50°C for 5 hours to obtain a seed directing agent; the components in the seed directing agent and their corresponding molar ratios are 2.8Na2O:Al2O3:17SiO2:400H2O:2TEABr;

[0037] Sodium hydroxide, deionized water, seed crystal directing agent, sodium aluminate and silica sol were mixed in a weight ratio of 0.365:4.34:15.615:0.75:6.5, and stirred at 20°C for 20 hours to form a MOR synthesis system; the molar ratio of the MOR synthesis system was 6Na2O:Al2O3:30SiO2:500H2O;

[0038] The MOR synthesis system was transferred to a high-pressure reactor, crystallized at 170°C for 10 hours, and then filtered. The obtained solid was calcined at 550°C for 8 hours to obtain MOR powder. The particle size of the MOR powder was 8 to 10 μm.

[0039] Step 2: Take phthalic anhydride, urea and ammonium molybdate as precursors in a molar ratio of 20:10:1, grind the precursors to a particle size of 200-100 μm, then add anhydrous cuprous chloride in a molar ratio of anhydrous cuprous chloride to ammonium molybdate of 8:1, add MOR in a weight ratio of anhydrous cuprous chloride to MOR prepared in step 1 of 0.85:1, stir until mixed evenly, transfer to a three-necked flask, and add the precursor to kerosene in a weight volume ratio of 10 g:6. 0mL of kerosene was added, and the mixture was stirred and condensed and refluxed at 185°C for 4.5h under nitrogen atmosphere. When the color of the product in the bottle changed from malachite green to blue-green, the mixture was cooled, filtered, and washed with ethanol and acetone for 5 times respectively to obtain a solid collection. The solid collection was then boiled in a 2w% hydrochloric acid solution and a 2wt% sodium hydroxide solution in turn, and finally washed with deionized water for 5 times and dried at 80°C to obtain a CuPcs / MOR composite photocatalytic material, represented by: CuPcs 0.85 / MOR1.

[0040] Example 2

[0041] This embodiment provides a method for preparing a CuPcs / MOR composite photocatalytic material, comprising the following steps:

[0042] Step 1: Take tetraethylammonium bromide, deionized water, sodium hydroxide, sodium aluminate and silica sol in a weight ratio of 1.02:17.36:0.32:0.57:8.5, mix tetraethylammonium bromide, deionized water, sodium hydroxide and sodium aluminate, add silica sol after stirring evenly, continue stirring at 25°C for 5.5 hours to obtain a reaction solution, transfer the reaction solution to a high-pressure reactor, age at 100°C for 15.5 hours to obtain an aged solution, cool to room temperature, mix the aged solution with diatomaceous earth in a weight ratio of 2:1, and dry at 60°C for 8 hours to obtain a seed directing agent; the components in the seed directing agent and their corresponding molar ratios are 2.8Na2O:Al2O3:17SiO2:400H2O:2TEABr;

[0043] Sodium hydroxide, deionized water, seed directing agent, sodium aluminate and silica sol were mixed in a weight ratio of 0.36:4.4:15.6:0.74:6.5, and stirred at 27°C for 25 hours to form a MOR synthesis system; the molar ratio of the MOR synthesis system was 6Na2O:Al2O3:30SiO2:500H2O;

[0044] The MOR synthesis system was transferred to a high-pressure reactor, crystallized at 170°C for 10 hours, and then filtered. The obtained solid was calcined at 550°C for 8 hours to obtain MOR powder. The particle size of the MOR powder was 8 to 10 μm.

[0045] Step 2: Phthalic anhydride, urea and ammonium molybdate are taken as precursors in a molar ratio of 22:10:1. The precursors are ground to a particle size of 200 to 100 μm. Anhydrous cuprous chloride is then added according to a molar ratio of anhydrous cuprous chloride to ammonium molybdate of 8.5:1. MOR is added according to a weight ratio of anhydrous cuprous chloride to MOR prepared in step 1 of 0.85:1. After stirring until the mixture is uniform, the mixture is transferred to a three-necked flask and the weight volume ratio of the precursor to kerosene is 10 g. : 65mL kerosene was added, stirred and condensed under reflux at 185°C for 4.5h under nitrogen atmosphere protection, and when the color of the product in the bottle changed from malachite green to blue-green, it was cooled, filtered, and washed with ethanol and acetone for 3 times respectively to obtain a solid collection, and then the solid collection was boiled in 2w% hydrochloric acid solution and 2wt% sodium hydroxide solution in turn, and finally washed with deionized water for 3 times and dried at 80°C to obtain a CuPcs / MOR composite photocatalytic material, represented by: CuPcs 0.85 / MOR 1.5 .

[0046] Example 3

[0047] This embodiment provides a method for preparing a CuPcs / MOR composite photocatalytic material, comprising the following steps:

[0048] Step 1: Take tetraethylammonium bromide, deionized water, sodium hydroxide, sodium aluminate and silica sol in a weight ratio of 1.02:17.36:0.32:0.57:8.5, mix tetraethylammonium bromide, deionized water, sodium hydroxide and sodium aluminate, add silica sol after stirring evenly, continue stirring at 30°C for 6 hours to obtain a reaction solution, and transfer the reaction solution to a high-pressure reactor, age at 100°C for 16 hours to obtain an aged solution, cool to room temperature, mix the aged solution with diatomaceous earth in a weight ratio of 2:1, and dry at 70°C for 10 hours to obtain a seed directing agent; the components in the seed directing agent and their corresponding molar ratios are 2.8Na2O:Al2O3:17SiO2:400H2O:2TEABr;

[0049] Sodium hydroxide, deionized water, seed directing agent, sodium aluminate and silica sol were mixed in a weight ratio of 0.4):4.36:16):0.745:6.5, and stirred at 35°C for 30 hours to form a MOR synthesis system; the molar ratio of the MOR synthesis system was 6Na2O:Al2O3:30SiO2:500H2O;

[0050] The MOR synthesis system was transferred to a high-pressure reactor, crystallized at 170°C for 10 hours, and then filtered. The obtained solid was calcined at 550°C for 8 hours to obtain MOR powder; the particle size of the MOR powder was 8-10 μm; Step 2, phthalic anhydride, urea, and ammonium molybdate were taken as precursors at a molar ratio of 25:10:1, and the precursors were ground to a particle size of 200-100 μm, and then anhydrous cuprous chloride was added according to a molar ratio of anhydrous cuprous chloride to ammonium molybdate of 9:1, and MOR was added according to a weight ratio of anhydrous cuprous chloride to MOR prepared in step 1 of 0.85:2, After stirring until the mixture is uniform, the mixture is transferred to a three-necked flask, and kerosene is added according to the weight volume ratio of the precursor to kerosene of 10 g:70 mL. The mixture is stirred and condensed and refluxed at 185° C. for 4.5 hours under the protection of a nitrogen atmosphere. When the color of the product in the flask changes from malachite green to blue-green, the mixture is cooled, filtered, and washed with ethanol and acetone for 4 times respectively to obtain a solid collection. The solid collection is then boiled in a 2w% hydrochloric acid solution and a 2wt% sodium hydroxide solution in turn, and finally washed with deionized water for 4 times and dried at 80° C. to obtain a CuPcs / MOR composite photocatalytic material, represented as: CuPcs 0.85 / MOR2.

[0051] Example 4

[0052] The CuPcs / MOR composite photocatalytic material and its preparation method in this embodiment are different from those in Embodiment 1 only in that:

[0053] The weight ratio of anhydrous cuprous chloride in step 2 to MOR prepared in step 1 is 0.85:2.5, and the CuPcs / MOR composite photocatalytic material is obtained, which is represented by: CuPcs 0.85 / MOR 2.5 .

[0054] Example 5

[0055] The CuPcs / MOR composite photocatalytic material and its preparation method in this embodiment are different from those in Embodiment 1 only in that:

[0056] The weight ratio of anhydrous cuprous chloride in step 2 to MOR prepared in step 1 is 0.85:3, and the CuPcs / MOR composite photocatalytic material is obtained, which is represented by: CuPcs 0.85 / MOR3.

[0057] Comparative Example 1

[0058] The difference between Comparative Example 1 and Example 1 is that:

[0059] The synthesis process only includes step 2, and the weight ratio of anhydrous cuprous chloride to MOR is 0.85:0. The obtained composite photocatalytic material is represented by: CuPcs (monomer copper phthalocyanine).

[0060] Figure 1 Schematic diagram of the synthesis of CuPcs / MOR composite photocatalytic materials in Examples 1 to 5;

[0061] The CuPcs obtained by the technical solution of Example 3 0.85 / MOR2 composite photocatalytic material was characterized and compared with standard CuPcs and MOR. The obtained X-ray diffraction spectrum is shown in Figure 2 As shown. Figure 2 It was found that CuPcs 0.85 The peaks of / MOR2 at 2θ=6.97° and 23.73° are characteristic peaks of CuPcs, and the corresponding interplanar spacings are and This is consistent with the interplanar spacing parameters of β-crystalline CuPcs. From the figure, we can see that the index peaks at 2θ = 6.49°, 8.58°, 9.75°, 19.58°, 22.20°, 25.57°, 26.27°, 27.68° and 30.86° are related to the structure of MOR zeolite (JCPDS29~1257). By comparing the characteristic peak positions of monomer CuPcs and MOR, we found that the prepared CuPcs 0.85 / MOR2 is not affected by the synthesis conditions, and the prepared material has a high crystallinity, which proves the successful composite of CuPcs and MOR.

[0062] The CuPcs obtained by the technical solution of Example 3 0.85 The / MOR2 composite photocatalytic material was characterized and compared with CuPcs and MOR. The obtained Fourier transform infrared spectra are shown in Figure 3 shown.

[0063] from Figure 3 It was observed that the main characteristic peaks of MOR and CuPcs are in CuPcs 0.85 / MOR2 can be reflected in the infrared spectrum, 790cm -1 and 840cm -1 The peak at 1225 cm is attributed to the symmetric stretching vibration of the metal oxygen tetrahedron in the primary unit of MOR. -1 and 1050cm -1 The peak belongs to the asymmetric stretching vibration of the tetrahedron outside the zeolite framework, at 450cm -1 The peak at 1508cm is attributed to the Si-O bending vibration in zeolite. -1 、1456cm -1 and 1330cm -1 The absorption peak at 753 cm can be attributed to the stretching vibration of the C=C double bond and aromatic ring skeleton of CuPcs. -1and 726cm -1 The peak at 1000-1250 cm-1 belongs to the out-of-plane bending vibration of CH in CuPcs, which proves the formation of phthalocyanine ring in the composite material. -1 The typical vibration signal peak intensity at the position is too strong to suppress and cover the characteristic peak of CuPcs, indicating the vibration type of MOR. And CuPcs at 1648cm -1 The aromatic ring skeleton stretching vibration peak at CuPcs formed with MOR 0.85 / MOR2 composites, which can be explained by the interaction between CuPcs and MOR, proving that CuPcs and MOR are not simply mechanically mixed, and this interaction is the hydrogen bond between the imine group of CuPcs and the hydroxyl group on the surface of MOR. 0.85 / Composition information of MOR2 nanocomposites.

[0064] The CuPcs obtained by the technical solution of Example 3 0.85 The / MOR2 composite photocatalytic material was characterized and compared with CuPcs and MOR. The obtained XPS full spectrum is shown in Figure 4 , Figure 5 shown. Figure 4 (a) CuPcs, (b) MOR and (c) CuPcs prepared in Example 3 0.85 / MOR2 composite photocatalytic material XPS full spectrum; Figure 5 (a) CuPcs and (b) CuPcs prepared in Example 3 0.85 High-resolution Cu2p spectrum of / MOR2 composite photocatalytic material;

[0065] Depend on Figure 4 It can be seen that there are Cu2P, C1S, and N1S peaks in CuPcs, which proves the presence of Cu, N, and C elements in the sample. 0.85 / Cu2P, C1S, and N1S peaks can be observed in MOR2, proving the successful preparation of CuPcs. Figure 5 The peak at 935 eV in the spectrum corresponds to Cu2P 3 / 2 , the peak at 957 eV is attributed to Cu 2P 1 / 2 , these peaks belong to the characteristic peaks of Cu in CuPcs. 0.85 In the Cu spectrum of / MOR2, in addition to the characteristic peak of Cu in CuPcs, two other peaks appeared at 933eV and 952eV, which were respectively attributed to the 2P of Cu in CuO species. 3 / 2 and Cu2P 1 / 2The above results show that not only CuPcs exists in the composite material, but also CuO species are formed during the preparation process. The reason for the generation of CuO species is that under the action of the MOR electric field force, copper ions exist on the MOR surface and form copper oxide after reaction and post-treatment. Figure 2 No corresponding peaks were detected in the XRD spectrum of .

[0066] The CuPcs obtained by the technical solution of Example 3 0.85 The morphology of the / MOR2 composite photocatalytic material was characterized and compared with CuPcs and MOR. Figure 6 Results shown. Figure 6 (a, b) MOR, (c) CuPcs, (d) CuPcs prepared in Example 3 0.85 / MOR2 SEM (scanning electron microscope); (e) CuPcs 0.85 TEM image (transmission electron microscope image) of / MOR2; (f)CuPcs 0.85 HRTEM image (high magnification transmission electron microscope image) of / MOR2.

[0067] like Figure 6 As shown in (a), the synthesized MOR zeolite has a uniform size, with a particle size of 8 to 10 μm. Figure 6 (b) It can be seen that the synthesized MOR has a multi-layer structure with a large number of pores on the surface. The large specific surface area and abundant pores are conducive to the adsorption of gaseous substances. Figure 6 As can be seen in (c), CuPcs has a rod-like structure of uniform size. When CuPcs exists in a pure phase, the strong π-π interaction of the phthalocyanine compound causes the copper phthalocyanine nanorods to form aggregates, which hinders the contact between pollutants and them and inhibits the separation of carriers. When CuPcs is compounded with MOR, a large coating structure is formed, and they are stacked on each other. Figure 6 (d) CuPcs 0.85 The scanning electron microscope morphology of / MOR2 shows that compared with the slender nanorod-type CuPcs, the composite material has the characteristic morphology of both CuPcs and MOR.

[0068] like Figure 6 As shown in Figures 6(e) and 6(f), two types of lattice fringes can be seen in the figure, where the lattice spacing of 0.568nm belongs to the (102) crystal plane of CuPcs, while the lattice spacing of 0.232nm corresponds to the (111) crystal plane of a small amount of CuO on the surface of CuPcs. This is consistent with the XPS results. The transition zone formed between them indicates that CuPcs and CuO are in contact with each other.

[0069] The CuPcs obtained by the technical solution of Example 30.85 The morphology of the / MOR2 composite photocatalytic material was characterized and compared with CuPcs and MOR. The adsorption-desorption isotherm curves were shown in Figure 7 As shown, Figure 7 (a) CuPcs, (b) MOR and (c) CuPcs 0.85 N2 adsorption-desorption isotherm curve of / MOR2.

[0070] CuPcs, MOR and CuPcs 0.85 The specific surface areas of MOR2 are 47, 381 and 173 m 2 g -1 The results show that the surface area of ​​CuPcs can be effectively increased by combining CuPcs and MOR. 0.85 / MOR2 shows an H3 hysteresis loop and a type IV isotherm at p / p0 = 0.08-1.00, indicating the presence of mesopores and stacked pores in the composite. After the introduction of CuPcs, the structure of MOR remains unchanged. CuPcs 0.85 / MOR2 has a lower BET surface area than MOR, which is due to the close contact between CuPcs nanorods and MOR, which causes a decrease in specific surface area. This indirectly proves that MOR and CuPcs are not simply doped, and the close contact interface between them is conducive to charge transfer.

[0071] The photocatalytic degradation of NO2 by different CuPcs / MOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 5 was tested. Before the photocatalytic reaction, all samples were placed in a reactor and reacted in the dark for 60 minutes to achieve adsorption and desorption equilibrium. In order to ensure the accuracy of the experiment, an empty bottle was irradiated with light as a blank experiment (Blank). The synthesized samples were tested for photocatalytic degradation of NO2. The results are as follows: Figure 8 shown.

[0072] Figure 8 (a) is the degradation rate of NO2 by different CuPcs / MOR composite photocatalysts at 120 min, (b) is the degradation rate of CuPcs and CuPcs 0.85 / NO2 degradation rate of MOR2 versus time.

[0073] like Figure 8As shown in (a), under illumination, the degradation rate of the blank experiment was 3.52%. In order to understand the effect of MOR on the photocatalytic activity of CuPcs / MOR composite materials, CuPcs / MOR composite materials with different contents were used to remove NO2. In order to avoid the reduction of NO2 content caused by the adsorption of MOR zeolite, MOR monomer was tested. Under the same conditions, the removal rate of NO2 by MOR was only 10.51%. When the mass ratio of CuCl to MOR was lower than 0.85:2, it can be observed that the degradation rate of NO2 increased with the increase of MOR content, indicating that MOR in the catalytic system is conducive to the enrichment of reactants, and MOR can be used as an electron acceptor to induce the transfer of photoelectrons on CuPcs from its conduction band to MOR, which improves the charge transfer efficiency, is conducive to the generation of active substances, and improves the degradation rate of NO2. Therefore, the synergistic effect plays an important role in the photocatalytic reaction. However, too much MOR will hinder the active sites of CuPcs and affect the photocatalytic reaction. When the weight ratio of CuPcs / MOR was 0.85:2, the composite material showed the highest photocatalytic conversion rate of 71.38%. The overall degradation rate of pure phase MOR or CuPcs was significantly lower than that of CuPcs. x / MOR y Composite material. In addition, the degradation rate of mechanically mixed pure phase MOR and CuPcs is also lower than that of the composite material. Since the photocatalytic active center of CuPcs and the adsorption site of MOR are separated from each other, it is not conducive to the enrichment of NO2, which reduces the chance of contact between CuPcs and NO2 molecules and reduces the degradation rate of NO2 by CuPcs / MOR composite photocatalytic material. This reflects that the adsorption performance of mordenite as a carrier can improve the degradation performance of photocatalytic materials for pollutants, which also proves that there is an interaction between CuPcs and MOR, and it is not a simple mechanical mixture.

[0074] Compare CuPcs 0.85 / MOR2 and CuPcs photocatalytic performance, such as Figure 8 (b) shows the NO2 degradation rate over time. Compared with pure CuPcs, the composite material exhibits a faster degradation response speed and higher degradation efficiency. CuPcs can be observed in the first 60 min. 0.85 / MOR2 rapidly degraded NO2, with a degradation rate of nearly 66.72%, which almost plateaued after 80 min, which may be caused by the accumulation of reaction intermediates blocking the photocatalytic active sites, hindering adsorption and degradation.

[0075] The CuPcs obtained by the technical solution of Example 3 0.85 The photocatalytic stability test of / MOR2 composite photocatalyst material obtained the following results: Fig. 9 As shown, Fig. 9CuPcs 0.85 / The recycling results of MOR2.

[0076] CuPcs 0.85 The / MOR2 composite photocatalyst was recycled four times to test its photocatalytic stability. Fig. 9 As shown, with the increase of reaction times, CuPcs 0.85 / MOR2 gradually decreases in efficiency, which is due to the CuPcs 0.85 The products accumulate on the surface of / MOR2, causing the photocatalytic active sites to be covered, resulting in a decrease in the utilization rate of light energy.

[0077] At the same time, the CuPcs 0.85 The morphology of the / MOR2 composite photocatalytic material before and after the reaction was detected, and the following results were obtained: Fig.10 The results shown, Fig.10 (a) CuPcs 0.85 (a) Scanning electron micrographs of the / MOR2 composite photocatalytic material before and (b) after the reaction. Fig.10 (c) CuPcs 0.85 / X-ray diffraction patterns of MOR2 before and after reaction.

[0078] from Fig.10 The accumulation of products can be observed in (a) and (b), but the characteristic morphology of the composite material has not changed after the reaction, and CuPcs nanorods and bulk mordenite can be seen. Fig.10 As shown in (c), after the photocatalytic reaction, CuPcs 0.85 The intensity of the X-ray diffraction pattern of CuPcs / MOR2 decreased, but the positions of the characteristic peaks corresponding to CuPcs and MOR did not change, confirming that CuPcs 0.85 / MOR2 relative stability of the composite photocatalytic material structure.

Claims

1. A method for preparing a CuPcs / MOR composite photocatalytic material, characterized in that: The following steps are involved: Step 1: Sodium hydroxide, deionized water, seed directing agent, sodium aluminate and silica sol are mixed in a weight ratio of (0.36-0.4): (4.34-4.4): (15.6-16): (0.74-0.75): 6.5, and stirred at 20-35° C. for 20-30 hours to form a MOR synthesis system; The MOR synthesis system was transferred to a high-pressure reactor, crystallized at 170°C for 10 h, and then filtered. The obtained solid was calcined at 550°C for 8 h to obtain MOR powder. The components in the seed directing agent and their corresponding molar ratios are 2.8Na2O:Al2O3:17SiO2:400H2O:2TEABr; Step 2, phthalic anhydride, urea, and ammonium molybdate are taken as precursors in a molar ratio of (20-25):10:1, the precursors are ground, and then anhydrous cuprous chloride is added according to a molar ratio of anhydrous cuprous chloride to ammonium molybdate of (8-9):1, and MOR is added according to a weight ratio of anhydrous cuprous chloride to MOR prepared in step 1 of 0.85:(1-3), stirred until mixed evenly, and then transferred to a three-necked flask, and kerosene is added according to a weight volume ratio of the precursor to kerosene of 10g:(60-70)mL, and stirred and condensed and refluxed at 185°C under nitrogen atmosphere protection for 4.5h. When the color of the product in the bottle changes from malachite green to blue-green, cool, filter, and wash to obtain a solid collection, and then boil the solid collection in 2w% hydrochloric acid solution and 2wt% sodium hydroxide solution in turn, and finally wash and dry to obtain a CuPcs / MOR composite photocatalytic material.

2. The method for preparing the CuPcs / MOR composite photocatalytic material according to claim 1, characterized in that: The preparation steps of the seed directing agent described in step 1 include: Tetraethylammonium bromide, deionized water, sodium hydroxide, sodium aluminate and silica sol are taken in a weight ratio of 1.02:17.36:0.32:0.57:8.5, tetraethylammonium bromide, deionized water, sodium hydroxide and sodium aluminate are mixed, and silica sol is added after stirring evenly. After continuing to stir at 20-30°C for 5-6 hours, a reaction solution is obtained, and the reaction solution is transferred to a high-pressure reactor, aged at 100°C for 15-16 hours to obtain an aged solution, and after cooling to room temperature, the aged solution is mixed with diatomaceous earth in a weight ratio of 2:1, and dried to obtain a seed directing agent.

3. The method for preparing the CuPcs / MOR composite photocatalytic material according to claim 2, characterized in that: The drying condition is drying at 50-70° C. for 5-10 hours.

4. The method for preparing the CuPcs / MOR composite photocatalytic material according to claim 1, characterized in that: The molar ratio of each component and its corresponding system in the MOR synthesis system described in step 1 is 6Na2O:Al2O3:30SiO2:500H2O.

5. The method for preparing the CuPcs / MOR composite photocatalytic material according to claim 1, characterized in that: The particle size of the MOR powder described in step 1 is 8 to 10 μm.

6. The method for preparing the CuPcs / MOR composite photocatalytic material according to claim 1, characterized in that: The precursor described in step 2 is ground to a particle size of 200-100 μm.

7. The method for preparing the CuPcs / MOR composite photocatalytic material according to claim 1, characterized in that: The cleaning described in step 2 is to use ethanol and acetone to clean for 3 to 5 times respectively.

8. The method for preparing the CuPcs / MOR composite photocatalytic material according to claim 1, characterized in that: The washing in step 2 is washing with deionized water for 3 to 5 times.

9. A CuPcs / MOR composite photocatalytic material prepared by the method according to any one of claims 1 to 8.

10. Use of the CuPcs / MOR composite photocatalytic material as claimed in claim 9 in photocatalytic elimination of NOx.